2021
DOI: 10.1017/s0007114521004773
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk–benefit assessment of Portuguese fish and other seafood species consumption scenarios

Abstract: Portugal has high fish/seafood consumption, which may have both risks and benefits. This study aims to quantify the net health impact of hypothetical scenarios of fish/seafood consumption in the Portuguese population using a risk-benefit assessment methodology. Consumption data from the National Food, Nutrition and Physical Activity Survey 2015-2016 (n=5811) was used to estimate the mean exposure to methylmercury and EPA+DHA in the current and the alternative scenarios considered. Alternative scenarios (alt) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
0
1
Order By: Relevance
“…Unlike other studies, a low frequency of fish consumption was found 2,28 . In fact, it is known that the main motivating factors for the purchase of fish are the species, the price, and health, and that the importance of factors differs between social classes, with the price being more important for social classes with lower incomes 29 .…”
Section: ) -contrasting
confidence: 83%
“…Unlike other studies, a low frequency of fish consumption was found 2,28 . In fact, it is known that the main motivating factors for the purchase of fish are the species, the price, and health, and that the importance of factors differs between social classes, with the price being more important for social classes with lower incomes 29 .…”
Section: ) -contrasting
confidence: 83%